MOBILE COURTS IN MARRIAGE VALIDATION (ITSBAT NIKAH) CASES AND THEIR CONTRIBUTION TO ACCESS TO JUSTICE AT THE SUNGGUMINASA RELIGIOUS COURT - Nadia Hamkan Bugis (MADDIKA : Journal of Islamic Family Law, 2026)
There are still many married couples in Indonesia who have entered into marriage under Islamic law but have not officially registered their marriages and therefore lack legal certainty (nikah siri). This situation has led to a growing public need for the resolution of itsbat nikah (judicial marriage validation) cases through mobile court proceedings (sidang keliling) as a means of expanding access to justice. This study aims to analyze the mechanism for resolving itsbat nikah cases through mobile court proceedings at the Sungguminasa Religious Court, identify the factors that support and hinder their implementation, and analyze the role of mobile court proceedings in ensuring access to justice and legal certainty. This study employed a qualitative approach using field research. Data were collected through observations, interviews with judges, court clerks, and court staff, as well as document review, and were subsequently analyzed using descriptive qualitative methods. The findings indicate that the mechanism for resolving itsbat nikah cases through mobile court proceedings is implemented in accordance with the procedural law governing the Religious Courts, with the principal distinction being that the hearings are conducted outside the court building. The effectiveness of their implementation is supported by the availability of budgetary allocations, inter-agency coordination, the readiness of human resources, the utilization of the e-Court system, and increasing public legal awareness. Meanwhile, the main obstacles include geographical conditions, the absence of parties or witnesses, and incomplete administrative documents. These findings demonstrate that mobile court proceedings function not only as a mechanism for resolving itsbat nikah cases but also as an effective model of judicial service that expands access to justice and strengthens legal certainty through integrated institutional governance, inter-agency collaboration, and more accessible legal services for the community.